Trypanosoma congolense: In Vitro Culture and Transfection. Issue 1 (1st February 2019) - Kay, Chris; Peacock, Lori; Gibson, Wendy
Abstract: Trypanosoma congolense, together with T. vivax and T. brucei, causes African animal trypanosomiasis (AAT), or nagana, a livestock disease carried by bloodsucking tsetse flies in sub‐Saharan Africa. These parasitic protists cycle between two hosts: mammal and tsetse fly. The environment offered by each host to the trypanosome is markedly different, and hence the metabolism of stages found in the mammal differs from that of insect stages. For research on new diagnostics and therapeutics, it is appropriate to use the mammalian life cycle stage, bloodstream forms. Insect stages such as procyclics are useful for studying differentiation and also serve as a convenient source of easily cultured, non‐infective organisms. Here, we present protocols in current use in our laboratory for the in vitro culture of different life cycle stages of T. congolense —procyclics, epimastigotes, and bloodstream forms—together with methods for transfection enabling the organism to be genetically modified. © 2019 by John Wiley & Sons, Inc.